Interest rate pass-through in Nigeria: An asymmetric cointegration approach - Aliyu Alhaji Jibrilla; Dahiru H. Balami (CBN Journal of Applied Statistics, 2022)
This paper empirically examines the pass-through of the Central Bank of Nigeria policy rate to commercial banks' retail rates. The study covers the pre-liberalization (1962M01-1987M07) and post-liberalization (1987M08-2020M09) periods, and em- plys asymmetric cointegration and error-correction modelling approach. The empir- ical results indicate that the pass-through is incomplete during both periods, though, it is larger during the pre-liberalization period. The study further reveals that the banking crises lead to an increase in the lending rate in the long and short run. The effect of the crises on the deposit rate is also positive but only significant in the short run. The empirical analysis demonstrates that all the threshold cointegration tests for the two sample periods exhibit asymmetric behaviour. The retail loan/lending rate adjustment to changes in the policy rate during both periods appears asymmetric with upward rigidity. The finding supports the adverse customer reaction hypothesis, suggesting that banks are more rigid in raising loan rates than reducing them. The results also support customer reaction on the deposit side, showing among others, downward rigidity in deposit rates in both periods. Therefore, the study recommends that the monetary authorities should strengthen monetary operations to ensure effi- cient transmission of monetary policy rate. There is also a need for measures that can enhance competitiveness in the banking sector and improve the efficacy of the in- terest rate channel. More commitments to preventing a systemic crisis in the industry and those that can effectively contain unavoidable ones are also desirable.
Keywords: C21; C22; E58; 330; Banking crisis; lending rate; liberalization; policy rate; threshold autore- gressive